2016
DOI: 10.3916/c48-2016-09
|View full text |Cite
|
Sign up to set email alerts
|

Youth and the third sector media in Spain: Communication and social change training

Abstract: The aim of this paper is to examine the role of community, free and university media in Spain as tools for media literacy and as instruments for creating a more critical and communicative citizenry. After a conceptual section, we analyse training processes in this area with regard to the general population and their reference communities, devoting particular emphasis to the involvement of young people. The triangulation research method was based on quantitative (a survey) and qualitative (focus groups) techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
1
0
4
Order By: Relevance
“…La EPEC se presenta como un instrumento cuantitativo capaz de medir de manera válida y confiable los factores subyacentes del EC en la población universitaria. Por lo que la información producida puede contribuir a orientar estrategias que mejoren condiciones para el fortalecimiento del EC considerando a los jóvenes como actores protagónicos del proceso (Lema-Blanco, Rodríguez-Gómez, & Barranquero-Carretero, 2016;Saeteros-Hernández, Pérez-Piñero, & Sanabria-Ramos, 2018).…”
Section: Discussionunclassified
“…La EPEC se presenta como un instrumento cuantitativo capaz de medir de manera válida y confiable los factores subyacentes del EC en la población universitaria. Por lo que la información producida puede contribuir a orientar estrategias que mejoren condiciones para el fortalecimiento del EC considerando a los jóvenes como actores protagónicos del proceso (Lema-Blanco, Rodríguez-Gómez, & Barranquero-Carretero, 2016;Saeteros-Hernández, Pérez-Piñero, & Sanabria-Ramos, 2018).…”
Section: Discussionunclassified
“…The research has found that using social networks such as Twitter could facilitate learning as well as communication with students. There are three aspects that media literacy can address within the educational sector: firstly, it can open more sources, agendas and facts associated with the commercial benefits and their effect on corporate media; secondly, the right to publish to citizens to educate and generate projects through the use of communication; and lastly, as a source of alternative media for both the critical reception of media messages and the audio/visual products created by communities themselves (Lema-Blanco, Rodríguez-Gómez & Barranquero-Carretero, 2016). However, Camilia et al (2013) indicate that Nigerian students used social media for studying, but it had no impact on their learning even though they spent more time with it.…”
Section: Defining Social Mediamentioning
confidence: 99%
“…Al respecto, la pedagogía crítica plantea que la lectura como herramienta de aprendizaje, posibilita la construcción de hipótesis, la elaboración de inferencias y la interacción analítica con la información, habilidades cognitivas que por sus implicaciones cooperan no solo con la toma de posición frente al conocimiento científico, sino además, con la creación de condiciones para la producción de saber, requisito elemental que desde el punto de vista académico abre la brecha para ingresar oportunamente a la producción de conocimiento generado en las comunidades científicas (Carlino, 2003;Lema, Rodríguez, Barranquero, 2016;Morales, 2017).…”
Section: Investigar Y Leer En La Universidadunclassified